2018
DOI: 10.1136/esmoopen-2017-000313
|View full text |Cite
|
Sign up to set email alerts
|

Updated survival outcomes of NEJ005/TCOG0902: a randomised phase II study of concurrent versus sequential alternating gefitinib and chemotherapy in previously untreated non-small cell lung cancer with sensitive EGFR mutations

Abstract: BackgroundThe North-East Japan Study Group (NEJ) 005/Tokyo Cooperative Oncology Group (TCOG) 0902 study has reported that first-line concurrent and sequential alternating combination therapies of an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (gefitinib) plus platinum-based doublet chemotherapy (carboplatin/pemetrexed) offer promising efficacy with predictable toxicities for patients with EGFR-mutant non-small cell lung cancer. However, overall survival (OS) data were insufficient in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 23 publications
3
27
1
Order By: Relevance
“…In the present study, the OS of the combination group was 36.0 months, which was shorter than that in the NEJ005 study (41.9 months) [10]. This difference might be related to the different maintenance treatment regimens applied.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…In the present study, the OS of the combination group was 36.0 months, which was shorter than that in the NEJ005 study (41.9 months) [10]. This difference might be related to the different maintenance treatment regimens applied.…”
Section: Discussioncontrasting
confidence: 75%
“…In the present prospective, randomized, controlled trial, we found that PFS in the combination group was significantly longer than that in the icotinib group, and moreover, the ORR and DCR in the combination group were significantly higher than those in the icotinib group. The NEJ005 study compared a concurrent regimen and a sequential alternating regimen for the combination of gefitinib and chemotherapy [10,11]. Our in vitro studies suggested that the sequential administration of pemetrexed followed by icotinib exerted a synergistic effect on EGFR-mutant human lung adenocarcinoma cell lines [16], and that the volume and weight of tumor xenografts in the sequential pemetrexed followed by icotinib group were significantly smaller than sequential icotinib followed by pemetrexed group [14].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…72.4%, HR 0.6; 95% CI: 0.41–0.89, p = 0.005), whether single agent Pembrolizumab is enough for PD‐L1 high expressed patients or whether extra chemotherapy would have additional benefit remains a popular topic. We might refer to the result of NEJ009, which was the first phase III clinical trial that evaluated the combination of EGFR‐TKI and chemotherapy compared to TKI alone for EGFR mutated patients as first‐line therapy . The results highlighted the combination strategy as an optimal; it would prolong not only the PFS time (20.9 m vs .…”
Section: Discussionmentioning
confidence: 99%